The food security of residents and refugees of Ukraine after the Russian invasion - Olha Nimko; Leonie Hodel; Adelina Chandra; Rachael Garrett (Scientific Reports)
Abstract In this paper, survey evidence is used to examine the food security impacts of the 2022 Russian invasion of Ukraine. We focus on both residents of Ukraine and those fleeing to one of the wealthiest countries in Europe, Switzerland. Our questionnaire was sent to both Ukrainian residents and migrants to Switzerland between October 2022 and February 2023. 80% of respondents (n = 1267) indicated that they faced some form of food insecurity, most commonly an inability to eat balanced meals and/or running out of food without being able to buy more. Yet the incidence of more severe forms of food insecurity, including cutting and skipping meals for multiple months, eating less than needed, and feeling hungry without eating, affected more than 20% of the surveyed populations in both countries. Food insecurity for both residents of Ukraine and refugees in Switzerland is significantly more severe for households who perceive themselves to have below average income. In Ukraine higher food insecurity is identified in the conflict’s frontline regions and among larger households with less domestic food production. In Switzerland, women report lower access to many coping mechanisms (producing, trading, or borrowing food). This study underscores the urgent need for improved food programs in conflict zones as well as countries that host refugees, particularly where domestic food prices are very high and language barriers reduce income opportunities.